How Can A Man Control His Thoughts, Desires, And Passions? - Vereen, Bob. (Colorado Springs, CO : WaterBrook Press, 2004)
Includes bibliographical references (p. [101]).
Keywords: BIBLE STUDY RESOURCES; CHRISTIAN EDUCATION; BIBLE STUDIES